MYC is a regulator of androgen receptor inhibition-induced metabolic requirements in prostate cancer - Preston D. Crowell; Jenna M. Giafaglione; Anthony E. Jones; Nicholas M. Nunley; Takao Hashimoto; Amelie M.L. Delcourt; Anton Petcherski; Raag Agrawal; Matthew J. Bernard; Johnny A. Diaz; Kylie Y. Heering; Rong Rong Huang; et al. (Cell Reports, 2023)
Summary: Advanced prostate cancers are treated with therapies targeting the androgen receptor (AR) signaling pathway. While many tumors initially respond to AR inhibition, nearly all develop resistance. It is critical to understand how prostate tumor cells respond to AR inhibition in order to exploit therapy-induced phenotypes prior to the outgrowth of treatment-resistant disease. Here, we comprehensively characterize the effects of AR blockade on prostate cancer metabolism using transcriptomics, metabolomics, and bioenergetics approaches. The metabolic response to AR inhibition is defined by reduced glycolysis, robust elongation of mitochondria, and increased reliance on mitochondrial oxidative metabolism. We establish DRP1 activity and MYC signaling as mediators of AR-blockade-induced metabolic phenotypes. Rescuing DRP1 phosphorylation after AR inhibition restores mitochondrial fission, while rescuing MYC restores glycolytic activity and prevents sensitivity to complex I inhibition. Our study provides insight into the regulation of treatment-induced metabolic phenotypes and vulnerabilities in prostate cancer.